Genome-Wide Association Mapping Identifies Novel Panicle Morphology Loci and Candidate Genes in Sorghum - Wang, Lihua; Upadhyaya, Hari D.; Zheng, Jian; Liu, Yanlong; Singh, Shailesh Kumar; Gowda, C. L. L.; Kumar, Rajendra; Zhu, Yongqun; Wang, Yi-Hong; Li, Jieqin (Frontiers in Plant Science, 2021)
Panicle morphology is an important trait in racial classification and can determine grain yield and other agronomic traits in sorghum. In this study, we performed association mapping of panicle length, panicle width, panicle compactness, and peduncle recurving in the sorghum mini core panel measured in multiple environments with 6,094,317 single nucleotide polymorphism (SNP) markers. We mapped one locus each on chromosomes 7 and 9 to recurve peduncles and eight loci for panicle length, panicle width, and panicle compactness. Because panicle length was positively correlated with panicle width, all loci for panicle length and width were co-localized. Among the eight loci, two were on chromosomes 1, 2, and 6, and one each on chromosomes 8 and 10. The two loci on chromosome 2, Pm 2-1 and Pm 2-2, were detected in seven and five out of 11 testing environments, respectively. Pm 2-2 co-localized with panicle compactness. Candidate genes were identified from both loci. The rice Erect Panicle2 (EP2) ortholog was among the candidate genes in Pm 2-2. EP2 regulates panicle erectness and panicle length in rice and encodes a novel plant-specific protein with unknown functions. The results of this study may facilitate molecular identification of panicle morphology-related genes and enhancement of yield and adaptation in sorghum.